Navigating the era of disruption: How emotions can prompt job crafting behaviors - Barclay, Laurie J.; Kiefer, Tina; El Mansouri, Mouna (Human Resource Management, 2022)
AbstractEnvironmental disruptions can disturb the status quo. This can create the need for employees to navigate rapidly evolving demands in their work environment, often before formalized strategic plans can be developed and/or implemented. As such, understanding how employees experience and respond to these disruptions is critical for effective strategic human resource management. Drawing on appraisal theories of emotion, we argue that employees' appraisals of how the disruption has impacted their work can elicit discrete emotions (e.g., frustration and pride). In turn, these emotions can encourage employees to address challenges and opportunities by engaging in job crafting behaviors. Importantly, job crafting behaviors can have implications for subsequent employee outcomes (e.g., performance and well‐being). We test our predictions using a three‐wave survey (N = 402) in the context of the COVID‐19 pandemic—an unexpected environmental disruption that sparked rapid change. Theoretically, our findings provide insight into why and how employees can self‐initiate changes to their jobs in response to environmental disruptions as well as how job crafting behaviors impact employee outcomes. Practically, our findings provide insight and guidance to SHRM practitioners on how to effectively support and manage employees before, during, and after environmental disruptions.